Simulasi NRP Basic untuk Meningkatkan Kompetensi Resusitasi Neonatus - Rakhmalia Imeldawati; Ainun Ganisia; Kholifatul Ummah (Rena Cipta Mandiri, 2025)
Neonatal asphyxia is an early-life emergency that requires rapid, accurate, and standardized responses from primary health-care providers. This community service program aimed to improve knowledge and basic neonatal resuscitation skills through Neonatal Resuscitation Program (NRP) Basic simulation for primary health-care workers at Kebonsari Primary Health Center. The program included partner coordination, needs assessment, module and SOP/checklist development, a two-day training consisting of brief lectures, skills stations, clinical scenarios, and evaluation using pretest-posttest and OSCE/checklists. Twenty-five participants joined the training. The mean knowledge score increased from 58 to 84, reflecting a 26-point improvement. Twenty-two participants (88%) achieved competency in positive pressure ventilation, while 20 participants (80%) were competent in chest compression and team coordination stations. The activity also produced a package of SOPs, checklists, pocket algorithm cards, and equipment readiness checklists. NRP Basic simulation is useful to strengthen primary care readiness in the initial management of newborns with breathing difficulties.